DESKRIPSI KEMAMPUAN MEMBACA LITERAL DALAM CERITA FIKSI SISWA KELAS IV SEKOLAH DASAR NEGERI 36 PONTIANAK KOTA - Erma Yunita Sari; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe literal reading skills in fiction stories for fourthgrade students of 36 Pontianak City Elementary School. The method used inthis research is descriptive method. The source of this research is the fourthgrade students of SD Negeri 36 Pontianak City, totaling 25 students. Thedata analysis technique in this study used an instrument in the form of amultiple choice test, totaling 20 questions with 4 stages of activity, namelydata collection, data reduction, data presentation and conclusions. Theresults of the study, obtained an average literal reading ability in fictionstories is 76.6 in the (good) category. This means that judging from theresults of the ability of students in the very good category 3 people or 0.12%for the good category 18 or 0.72% and the category enough for 4 people or0.16%. Thus, it can be concluded that the literal reading ability in fictionstories of fourth grade students uses direct learning by working on multiplechoice questions. There are still some difficulties in reading literal students.Keywords: Description, Literal Reading Skills, Fiction Stories